Role of Public Organic Procurement Policies (POPP’s) in the implementation of organic food and farming strategies: lessons learnt from Denmark - Mikkelsen, Bent Egberg; Lundø, Martin (Raízes: Revista de Ciências Sociais e Econômicas, 2016)
Targeting public procurement policies has become an important goal for European policy makers since it is believed to contribute to more sustainable food systems and food consumption patterns. Food purchased by the public for institutions such as hospitals, care homes, universities, prisons, schools, armed forces and canteens represent a significant part of the food economy in European countries. As a result governments at different levels have adopted policies that promote organic food and farming in many countries. Since agencies and institutions of the public can be expected to be influential by setting good examples of food consumption, the food for the public plate has come to take a much more visible role in public service provision policymaking over the past decades. However, for such strategies to be effective the right policy mix is essential. This paper reports on the Danish case of Public Organic Procurement Policy (POPP’s) and its role in organic food and farming strategies. It gives a brief account on component of the policy mix including the setting up of a labelling system, a monitoring system for sales volumes and a foodservice workers training program. The paper examines the first results from the monitoring system and provides insight in the progress of POPP’s. It details the implementation and maintenance of the monitoring program and discusses the role of metrics in relation to other policy tools as well as the contribution that monitoring can make in terms of policy implementation.